(3GdHQgGf Ydi MbjbI eSCdI hbYJ Hjf CHj MGeO GdUZGfi hHjf efLei GdQi ajgG efGRYI hgi ef CYeGd GdCSWQdGHs - (3efUhQ Hf Ydj Hf YQGb, CHh fUQ,J (B425 (3g` s
(3ChdgG (B:s
(3bGd CHh fUQ efUhQ Efg hbYJ Edi ebGdI dCHi MGeO GdUZGfi jPcQ ajgG Cf efGRYI LQJ Hjfg hHjf efLei GdQi ai eSCdI ef eYQaI GdCSWQdGH s
(3BNQgG (B:s
(3hgh Ci LRA aQV ai LgI GdWGdY ef GdOGFQ GdJi HMO YQV Ebdje GdQhjI cGf GdLRA HeG ajg caGjI dgPG GdeYfi , hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B78(3C (B- (3U(B79(3Cs
(3HgG fXGe GdJYbjHIs
(3HgG CTcGd gfOSjIs
(3cJHJ Hbde eged GdfbW CMjGfkGs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs